Implementation Analysis of Digitally Pencak Silat Agility Instrument - Januar Sahri; Nurul Ihsan; Bafirman Bafirman; Asep Sujana Wahyuri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
This study aims to design an agility test instrument based on sensor technology that is specifically designed to suit the conditions of pencak silat athletes in the field. This research method is Research and Development with the research development steps Borg and Gall. The sample for the small-scale trial was 100 people, while the large-scale trial sample was 120 people. The sample of this study were athletes at Padang State University aged 19-23 years. Based on the development, the resulting tool is a prototype in the form of a rectangular 8 measuring 1x1 M and has 8 sensors in each corner which functions to calculate the number of steps of the athlete's stance which describes his agility. Expert validation shows that the percentage of the assessment is 91% which means that this measuring instrument has the category of